Potentials of blended learning in changing the delivery of literacy education and skills acquisition in Nigeria in the digital age (2023)
The potential for blended learning to change how literacy instruction and skill acquisition are delivered in Nigeria in the digital age, as well as its many advantages, are covered in the paper. Learning has become more appealing and efficient thanks to blended learning's flexibility and interactive features. Additionally, it has helped students access education and helped faculty members get ready for the digital age of employment. In essence, it improves teaching and learning opportunities, student academic accomplishment, and access to education for all. In order to strengthen our literacy education delivery in Nigeria in light of the Covid-19 pandemic's resurgence, blended learning must be included into the delivery of literacy education and the acquisition of skills. The concept of blended learning, a conceptual view of literacy in literature, a new construct of literacy and its recognition of its core values, a concept of skill acquisition, a theory of blended learning, roles of information and communication technology in blended learning effectiveness in the digital age, the challenges in integrating blended learning into Nigerian literacy education, and the conclusion are all explored in this paper. The report ends with suggestions for tactically implementing blended learning in Nigerian literacy and skill development